Pengaruh Penyuluhan Kanker Payudara Terhadap Minat Pemeriksaan Payudara Sendiri (Sadari) Pada Remaja SMAN 1 Jatinom - Fitri Nur Hapsari (2020)
The high mortality rate from breast cancer is caused by breast cancer patients coming to health services in an advanced stage and difficult to cure. This is because most women and adolescents are lack information about breast cancer prevention. Need health education about the importance of early detection of breast cancer, which can increase life expectancy. This research aims to determine the influence of breast cancer counseling on the interest of conducting breast self-examination in the students of SMAN 1 Jatinom Klaten. This type of research is pre-experimental research with a one group pre test-post test design approach. The research population is a member of teenage Red Cross, SMAN 1 Jatinom Klaten, the sample technique is a total sampling of 33 respondents. Data analysis using paired t-test obtained value P = 0.000 < α = 0.05. The results showed there is effect of breast cancer counseling to the interest of breast examination in adolescents of SMAN 1 Jatinom Klaten. After the education of health information on the importance of early detection of breast cancer, adolescents are expected to practice breast exams on a monthly basis, after menstruation.